2018
DOI: 10.1371/journal.pone.0209655
|View full text |Cite
|
Sign up to set email alerts
|

Surviving Ebola: A historical cohort study of Ebola mortality and survival in Sierra Leone 2014-2015

Abstract: BackgroundWhile a number of predictors for Ebola mortality have been identified, less is known about post-viral symptoms. The identification of acute-illness predictors for post-viral symptoms could allow the selection of patients for more active follow up in the future, and those in whom early interventions may be beneficial in the long term. Studying predictors of both mortality and post-viral symptoms within a single cohort of patients could also further our understanding of the pathophysiology of survivor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Of the 3,385 individuals studied, 223 (6.6%) were found to have some degree of HL using audiometric evaluation and survey instruments. 19,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Only one of 21 articles used audiometry to objectively measure HL. This study, by Rowe et al, 19 recruited convalescent Ebola survivors and household contacts following the conclusion of the 1995 Ebola outbreak in Kikwit, DRC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 3,385 individuals studied, 223 (6.6%) were found to have some degree of HL using audiometric evaluation and survey instruments. 19,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Only one of 21 articles used audiometry to objectively measure HL. This study, by Rowe et al, 19 recruited convalescent Ebola survivors and household contacts following the conclusion of the 1995 Ebola outbreak in Kikwit, DRC.…”
Section: Resultsmentioning
confidence: 99%
“…The remainder of the articles that described HL as sequelae of Ebola relied on questionnaires or self-report of symptoms. [36][37][38][39][40][41][42][43][44][45][46]50,[52][53][54] The proportion of individuals reporting HL in these articles varied widely, from 0% to 22%. In these studies relying on self-report, HL typically arose late in the course of the disease and persisted throughout recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Little is known regarding hearing loss in Post-EVD Syndrome. A literature review conducted in 2018 found that reports of hearing impairment in EVD survivors varied from 0% to as high as 66% [ 32 , 33 , 39 41 ]. However, only one of the studies included in this review included any objective measurement to assess for the presence of this symptom, which may leave many cases of hearing loss undetected [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult studies have reported that increased VL, AST, ALT, CK, bilirubin, creatinine, urea, INR, and PTT were associated with mortality. 17 , 18 , 20 , 27 …”
Section: Discussionmentioning
confidence: 99%